If it's not what You are looking for type in the equation solver your own equation and let us solve it.
671-23=y
We move all terms to the left:
671-23-(y)=0
We add all the numbers together, and all the variables
-1y+648=0
We move all terms containing y to the left, all other terms to the right
-y=-648
y=-648/-1
y=+648
| -12(-2g-3)=84 | | 11^x+3=12 | | 4x–6=6+1x | | x/4-10=-2 | | 3(2d-)-2d=4(d-2)+5 | | –3(2n–5)=21(-12n+30) | | −8x+14=−2(4x−7 | | 8/8c+13=18 | | 6x+1=6x−8 | | 3.50+x=35 | | 8x+10=10× | | 7(3−k)=−3k+4 | | –7m=–8m+6 | | 2x9=35 | | 3-6x=4x+48-12x | | x-19.2=19.7 | | 2/5x–40=0 | | -2/3w+53=33 | | 8x+12=12×-8 | | ⅕x=1 | | 10+3x=4+2x | | 7x−9=3+27x | | 10+8=-3(9x-6 | | 4(x-5)2(x+15)=100 | | 7x−9=3x+27 | | 25=4(3x-8)-2(x+6)=x-9 | | 4+29=-3(3x-8) | | 3r-4-1=8 | | 18x=-21 | | 9−17x−7−4x=5 | | -11+20=-3(x+9) | | 3+x-5=9 |